Efficiency of community based intervention programme on keeping lowered weight - Petek, Davorina (Zdravstveno varstvo, 2011)
Objective: To establish the effectiveness of community based intervention on lowering and sustaining weight. Methods: We performed a longitudinal retrospective study in three primary care centres in Slovenia. 333 men aged 35to 65 and women aged 45 to 70 with body mass index higher than 25 kg/m2 and high risk for cardiovascular diseases or with body mass index higher than 30 kg/m2 were included. The data for the analysis were extracted from the forms of National cardio-vascular disease prevention programme. Long-term follow-up of their weight was performed 12 to 24 months after the intervention. Results:The inclusion criteria fulfilled 250 (75%) participants. During the programme the participantsć weightlowered by a mean 6.7 kg from 95.5 15.1 to 88.8 14.7 kg (7.1% of the entry body weight, 95% CI: -7.2 to -6.1 %). One to two years after the intervention 62.8% of the participants could not keep the weight they achieved during the intervention phase. Mean regain of the weight was 1.6 kg, (23% of the lost weight, 95% CI: 0.8 to 2.4 kg). Initial body weight of people, who long-term succeeded to keep achieved weight was higher than initial body weight of those people, who regained weight after the programme (t=3.490, P= 0.001) Gender and age did not show any statistically significant impact on long-term weight gain. Conclusions: The intervention programme was successful by the criteria that weight reduction should be at least 5-10%. Majority of the participants could not sustain the reduced weight, but the mean weight gain was less than one fourth of the weight, lost in the intervention period. Besides the interventions for weight reduction also the longterm programmes for sustaining the achieved weight loss are very important.
Keywords: debelost; družinska medicina; hujšanje; preventiva